Ghrelin is Related to Personality Differences in Reward Sensitivity and Impulsivity. (9th November 2017) - Ralevski, Elizabeth; Shanabrough, Marya; Newcomb, Jenelle; Gandelman, Erin; Hayden, Ryan; Horvath, Tamas L; Petrakis, Ismene
Abstract: Aims: Ghrelin, a feeding-related peptide mainly produced in the stomach, has been linked to reward mechanisms for food and drugs of abuse in addition to traits of impulsivity. This study is a secondary analysis of an existing data set designed to examine the direct relationships between fasting ghrelin levels and reward sensitivity/impulsivity in healthy social drinkers. Methods: Participants ( n = 20) were recruited from an original study examining the subjective effects of alcohol among social drinkers. Fasting ghrelin levels were collected at baseline. Personality measures (Behavioral Inhibition, Behavioral Activation, and Affective Response to Impending Reward and Punishment and Barratt Impulsiveness Scale) were administered at baseline to evaluate sensitivity to reward and punishment, and measure traits of impulsivity, respectively. Results: Fasting ghrelin levels were significantly related to reward sensitivity and impulsivity traits. Specifically, those with higher ghrelin levels were more sensitive to reward and were more impulsive (have lower self-control). Conclusions: The results indicate that individuals with higher levels of ghrelin are more sensitive to reward. In addition, they are less able to exercise self-control and to an extent more likely to act without thinking. This is the first study to report on the direct relationship between fasting ghrelin levels and personality characteristics such as reward sensitivity and aspects of impulsivity among healthy social drinkers. Short summary: Individuals with higher levels of fasting ghrelin are more sensitive to reward, but less sensitive to punishment. Higher ghrelin levels are also related to some aspects of impulsivity such as decreased self-control and increased likelihood of acting without thinking.